Analysis of Microplastics and Heavy Metals in Most Consumed Molluscs cultured in Can Gio Biosphere Reserve of Vietnam - Khuyen, Vo Thi Kim; Kim, Vo Thi Thien (Indonesian Journal of Chemical Analysis (IJCA), 2024)
Can Gio, designated in 2000, is the first Biosphere Reserve of Vietnam. In recent years, local agriculture, tourism, households, nearby industrial zones, and maritime transport have released substances into rivers flowing through Can Gio Mangrove to the East Sea and transported into creatures. This study aims to investigate microplastics and heavy metals in the famous seafood of Can Gio. A Raman microscope was used to identify microplastics from the tissue of oysters, grease snails, and clams after enzymatic treatment with trypsin. Heavy metals were quantified with ICP-MS after acidic treatment. As a result, microplastics were found in almost all samples, even up to 10 in a random individual of bivalve. Fibers dominated, especially from 30 to 150 µm long. The metal with the highest content was zinc, followed by copper, especially in oysters. Non-essential metals were also present in the soft tissue in the order As > Pb > Cd. The accumulation of metals in Can Gio’s molluscs was generally lower than in other regions and still in the allowed range for consumption of Vietnamese Standard. Although there have not been any Vietnamese regulations on the permissible level of microplastics for consumption, regular seafood intake will increase the risk of chronic poisoning and unknown disorders caused by the accumulation of microplastics and heavy metals.